Body knowledge : performance, intermediality, and American entertainment at the turn of the twentieth century - Simonson, Mary (Oxford University Press, 2013)
The performances and conceptions of art by women that emerged in American cities in the early 20th century were innovative, compelling, and deeply meaningful. This book examines these performances and the performers behind them, focusing particularly on the ways in which they negotiated turn-of-the-century American social and cultural issues, including technological developments and commodification, new modes of perception, evolving understandings of the body and the self, and shifting conceptions of gender, race, and sexual identity.